Concurrent Effects of Drought and Heat Stresses on Physio-Chemical Attributes, Antioxidant Status and Kernel Quality Traits in Maize (Zea mays L.) Hybrids - Yousaf, Muhammad Irfan; Riaz, Muhammad Waheed; Jiang, Yurong; Yasir, Muhammad; Aslam, Muhammad Zahid; Hussain, Sabir; Sajid Shah, Syed Awais; Shehzad, Aamar; Riasat, Gulfam; Manzoor, Muhammad Aamir; Akhtar, Imran (Frontiers in Plant Science, 2022)
Maize is one of the most important field crops considering its utilization as food, feed, fodder, and fuel. However, the sustainability of its production is under serious threat of heat and drought stresses, as these stresses could hamper crop growth, causing a significant loss to kernel yield. The research study was carried out at Maize and Millets Research Institute, Yusafwala-Sahiwal for two consecutive spring seasons (2019-20 & 2020-21) under a split-split plot design. The current study explained the individual and combined effects of drought and heat stresses on morphology, phenology, physiology, reactive oxygen species (ROS), antioxidant status, and kernel quality traits in four indigenous (YH-5482, YH-5427, YH-5404, and YH-1898) and one multinational maize hybrid (P-1543). Stress treatments, i.e., drought, heat, and drought+heat, were applied ten days before tasseling and lasted for 21 days. The results revealed the incidence of oxidative stress due to overproduction of Hydrogen peroxide; H2O2 (control: 1.9, heat+drought: 5.8), and Malondialdehyde; MDA (control: 116.5, heat+drought: 193), leading to reduced photosynthetic ability (control: 31.8, heat:16.5), alterations in plant morphology, decrease in kernel yield (control: 10865 kg ha-1, heat+drought: 5564 kg ha-1), and quality-related traits. Although all the stress treatments induced the accumulation of stress-responsive osmolytes and enzymatic antioxidants to cope with the negative impact of osmotic stress, the effect of combined drought + heat stress was much higher. The overall performance of indigenous maize hybrid YH-5427 was much more promising than the other hybrids, attributed to its better tolerance of drought and heat stresses. Such stress tolerance was attributed to maintaining photosynthetic activity, a potent antioxidant and osmolyte-based defense mechanisms, and minimum reductions in yield-related traits, which assured the maximum kernel yield under all stress treatments.